Charter of Freiburg of 1293: Burgomaster and Heads of Corporations - Pavel Blokhin (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The Charter of Freiburg, drawn up in 1293, marked the end of the reform of the city administration. The document also reflects the process of forming management structures for local workshops. Methods and materials. The main research method is comparative historical analysis. The provisions of the Charter of 1293 and early compilations of law are compared. Analysis. The position of the governing bodies of the trading corporations in the city and the powers of the Burgomaster and the SchultheiЯ are examined. Special attention is paid to the election of shop masters, heads of the workshops, and the burgomaster, who was the head of all the craftsmen’s associations in the city. The formation of management structures in the artisan environment led to the emergence of a new body of municipal government – the Public Council. It was made up of the local lord and members of the Junior and Senior Councils (the regular bodies of Freiburg’s self-government). Among other things, the Public Council held elections for shop masters, supervised their activities, and dismissed them if necessary. Unlike the heads of the craftsmen’s associations, the burgomaster was appointed directly by the lord. At the same time, the powers of the burgomaster went beyond the mere management of the town shops. Among other things, the burgomaster was the spokesman for the interests of the Junior Council and participated in its management activities. With the advent of the office of burgomaster, the former head of the town and supreme judge – the SchultheiЯ – lost a number of their administrative functions and part of their income. Results. The Charter of 1293 recorded the establishment of a municipal government in the city, which included the Senior (supreme legislative power) and Junior Councils (supreme supervisory, legislative power), the SchultheiЯ (supreme judicial power), and the burgomaster (management of the city’s crafts). The Freiburg workshops became self-governing craft corporations.